Maya kingship rupture and transformation from classic to postclassic times - Okoshi, Tsubasa; Chase, Arlen Frank 1953-; Nondédéo, Philippe; Arnauld, Marie-Charlotte 1948- (University Press of Florida, 2021)
"Examining changes to the institution of divine kingship from 750 to 950 CE in the Maya lowland cities, this volume presents a new way of studying the collapse of that civilization and the transformation of political systems between the Terminal Classic and Postclassic Periods"--
Keywords: Geschichte 750-950; Gesellschaft; Maya; König; Politisches System; Mayas / Kings and rulers; Mayas / History; Mayas; History; Konferenzschrift -- ¿Ruptura o transformatción de la realeza maya? Del Clásico al Posclásico -- 11.11.2017-14.11.2017 -- Kyoto